PENGARUH SUPERPARASITISME TERHADAP PERKEMBANGAN PROGENI PARASITOID Tetrastichus brontispae Ferriere - Husni Husni; Jauharlina, Jauharlina,; Amru Al Haraqal (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
The purpose of this research was to investigate effects of superparasitism rate on development of Tetrastichus brontispae progeny. In this research, each host (Brontispa longissima pupa) was exposed for different frequencies, i.e., 1, 3, 5, 7 and 9 times for female parasitoid. The result showed that the rate of superparasitism affected the number of progeny emergence, the developmental time of immature progeny, and sex ratio of progeny. The number of progeny emergence was increased as the increase of superparasitism rate. The number of progeny emergence from single oviposition host was 15, while from host exposed on female parasitoid for 3, 5, 7, and 9 times were 12, 5, 2 and 0, respectively. The developmental time of immature progeny was lengthened as the increase of superparasitism rate. Sex ratio of progeny was biased to female progeny as the increase of rate of superparasitism. The result of this research indicated that superparasitism gave negative effect on development of T. brontispae progeny.